Lari Mesi Alternatif Penanaman Kesadaran Konstitusi dan Sikap Toleransi Bagi Peserta Didik Sekolah Dasar - Hendrik Hermawan (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The purpose of implementing this learning is to instill constitutional awareness and tolerance for fourth grade students at the Wirosari 1 State Elementary School in 2020/2021 by using the Lari Mesi media. The type of scientific innovation used is the best practice method by testing the effectiveness of the Lari Mesi multimedia by analyzing the increase in constitutional awareness after and during learning. There was an increase in constitutional awareness of learning outcomes and observations from before using the Lari Mesi media to after using it, from only 30% of students who completed it to 89.71% who completed it.